Logistics Management Training GRC Roster for the Building Materials Industry in Desa Citeko - Rhiswandi, Rhandi; Sundari, Bella; Novia, Gita; Julianti, Indri; Fitri, Nuriya (Fakultas Kewirausahaan Universitas Garut, 2025)
The roster industry in Citeko Village, Plered District, Purwakarta Regency, serves as a key production center for architectural building materials. However, local enterprises face significant logistical challenges, particularly in manual and inefficient workforce rostering systems. This study aims to analyze the implementation of technology-based logistics management aligned with ISCEA (2021) principles to enhance operational efficiency and workforce well-being. The findings indicate that adopting digital systems such as e-rostering and dynamic scheduling can improve efficiency, reduce logistics costs, and strengthen the competitiveness of rural roster industries. Technology-driven logistics training is identified as a strategic step toward es tablishing an adaptive, efficient, and sustainable logistics system in Citeko.